Chatting Via Whats App for Developing Students’ Writing Skill - Naji, Zanaib Abbas (Journal of Tikrit University for Humanities, 2023)
The current study aims at examining whether text chatting via WhatsApp using mobile phones has any effect on the development of student’ writing skills. The experiment was held in the second half of 2022/2023 academic year, which lasted for two months. The current study uses quantitative theory. Pre and posttest was used in the study as a data collection tool. The data collected were analyzed using SPSS Software. Population consisted of all the 82 students of the third intermediate grade. The sample of the study consisted of 50 students who were chosen randomly by the researcher. The research divided the study sample into two groups (experimental and control), each group consisted equally of 25 students. Before conducting the experiment, the researcher conducted a pre-test to find out the both groups’ writing competency before starting the experiment. Two months later, the researcher conducted a post-test using the same test that was used before the experiment and under the same conditions, to see if there was, any statistically significant differences in the experimental students’ mean scores after using the new method of teaching. In other words, to find any development in the students’ performance using the text chat method via WhatsApp. After analyzing the data, the study revealed that there was a clear development in the students’ performance in favor of the experimental group students. This indicates that the use of text chat using WhatsApp had a positive and influential effect on developing the writing skill of the third intermediate grade students.